Otimização da produção de Cordyceps militaris em meio a base de melaço de cana e quantificação de compostos bioativos - Cerri, Maria Luísa (2021)
Cordyceps militaris is a fungus of growing popular and scientific interest due to its complex bioactive composition that gives it functions of pharmacological relevance. It is composed of molecules such as ergosterol, mannitol, adenosine, cordycepin and exopolysaccharides. Such bioactive molecules are traditionally produced with Cordyceps militaris frutification, a long and demanding process affected by productivity loss in a short period of time. This fungus mycelium also contains bioactive compounds although in a lower concentration. Even though, the mycelium production allows an easier upscale and therefore might show an advantage. This research proposes the use of sugarcane molasses (a by-product of the sugar industry) as main carbon source for Cordyceps militaris mycelium production. The optimization of the culture medium was based on the statistical analysis of the central composite arrangement (CCD) and the optimized medium determined was capable of producing 25.1 g.L-1 of biomass. Tests with the addition of olive oil and magnesium sulfate were carried out to test its effectiveness in the production of bioactive compounds. Folin-ciocalteau and DPPH (2,2-diphenyl-1-picryl-hydrazil) methods were used to evaluate phenolic compounds and antioxidant activity, respectively. Initial analyzes were performed in highperformance liquid chromatography coupled to mass spectrometry (LC / MS-MS), to identify possible masses in the extracts, compare and optimizing extraction methods aiming at the better detection of cordycepin. The extract produced from the liquid medium showed higher concentrations of phenolic compounds and antioxidant activity compared to the mycelial extract. The production of phenolic compounds in 60 days in an optimized medium is 50% higher than in 10 days. In comparison to the maintenance medium, the optimized medium has 14% more phenolic compounds (both with 60 days of cultivation). For DPPH, the best result was the extract from the liquid medium optimized with EC50 of 9.98 ml / L. Regarding the extractions, the best method was shown to be 15 partitions with ethyl acetate, as it is more selective to cordycepin, a compound of greatest interest, and to reduce the presence of other compounds that hinder its determination and may cause clogging of the spine. The use of molasses as a carbon source for C. militaris was validated in this study, as well as its ideal concentration and the increased production of phenolic compounds to the detriment of the maintenance medium.